2022
DOI: 10.1088/1361-6463/ac6e9e
|View full text |Cite
|
Sign up to set email alerts
|

Z-scheme SnC/HfS2 van der Waals heterojunction increases photocatalytic overall water splitting

Abstract: Z-scheme heterostructures are efficient photocatalysts due to their small forbidden bandgap and high redox reaction ability. This paper designed the SnC/HfS2 heterojunction and explored its band structure and photocatalytic properties for water decomposition based on density functional theory. Our results suggest that SnC/HfS2 heterostructure is a typical direct Z-scheme heterojunction, which can effectively separate carriers and possesses strong oxidation and reduction capabilities. The VBM of SnC approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 77 publications
2
11
0
Order By: Relevance
“…For instance, SnC/HfS 2 can only catalyze water splitting in extremely acidic conditions, while SnC/HfSSe and SnC/PtSe 2 fail to exhibit catalytic activity without external energy input. 23–25 Therefore, a convenient strategy to enhance the photocatalytic performance of SnC ML is required. Here, the strategy of doping group IV elements into SnC ML is being attempted, in which a single Si or Ge atom is doped into the SnC supercell that consists of 12 Sn and 12 C atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, SnC/HfS 2 can only catalyze water splitting in extremely acidic conditions, while SnC/HfSSe and SnC/PtSe 2 fail to exhibit catalytic activity without external energy input. 23–25 Therefore, a convenient strategy to enhance the photocatalytic performance of SnC ML is required. Here, the strategy of doping group IV elements into SnC ML is being attempted, in which a single Si or Ge atom is doped into the SnC supercell that consists of 12 Sn and 12 C atoms.…”
Section: Resultsmentioning
confidence: 99%
“…However, these photocatalysts often require external energy input and/or acidic conditions due to the high barrier in HER from the SnC ML. 21–26 Therefore, further investigations are necessary to enhance the photocatalytic activity of SnC ML-based vdWHSs for the development of high-performance photocatalysts. Considering its atomic structure, band edge positions, and light absorption capability within the solar spectrum, ZrS 2 ML may be a desirable candidate for the construction of an SnC ML-based vdWHS.…”
Section: Introductionmentioning
confidence: 99%
“…X-S (X = Zr, Hf) bond lengths are 2.57 and 2.54 Å, respectively, agreeing well with other reports. [36][37][38] It can be concluded that the lattice mismatch ratio (d) of InN/XS 2 (X = Zr, Hf) is less than 1.5%, according to the formula: d = |a XS 2 À a InN |/a XS 2 which is favorable for the synthesis of heterojunctions.…”
Section: Geometry and Stability Of Heterojunctionsmentioning
confidence: 99%
“…46 Besides, a theoretical study suggests that the SnC/HfS 2 vdW heterostructure is a typical direct Z-scheme vdW heterostructure with high capture capacity of solar energy in the infrared region, making it a potentially promising photocatalyst for water splitting. 47 Interestingly, by screening the previous high-throughput computational screening database of Janus 2D III–VI van der Waals heterostructures, Al 2 SeTe/GaSe and Al 2 SeTe/InS heterostructures are found to show a distinguished direct band gap electronic structure belonging to type-II band alignment, which shows their potential application as Z-scheme photocatalysts for water splitting. 43 Therefore, a systematic study of Al 2 SeTe/GaSe- and Al 2 SeTe/InS-based vdW heterostructures for potential photocatalytic applications is of great interest and importance.…”
Section: Introductionmentioning
confidence: 99%